Goop soup - Lubar, David (Lubar, David. Nathan Abercrombie, accidental zombie, 2010)
Nathan and his friends Abigail and Mookie are asked to investigate when greasy green globs of goop start oozing from the town's faucets, but the trail soon leads to the sewers of East Craven.